Optimized design of satellite-borne multiple power supply - Xu Juan; Wang Zhengzhi (Dianzi Jishu Yingyong)
Because of the special environment of the satellite-borne power supply, there are not many effective ways to dissipate heat, so the power density and efficiency of the power supply are more demanding. And because of its strict requirements for components, the choice of circuits and components are also correspondingly limited. This paper mainly introduces the design of flyback converter optimized on the basis of the original multi-channel power supply, and analyzes its working principle, then designs a new satellite-borne multiple power supply. Finally, the efficiency of the newly designed multiplex power supply is compared with that of the original multiplex power supply, and the feasibility of the optimized power supply design is verified.